The versatile film projectionist: How to show films and serve the people in the 17 years period, 1949–1966. Issue 3 (1st September 2016) - Zhou, Chenshu
ABSTRACT: In the early years of the People's Republic of China, the state recognized the power of film as a mass medium and expanded a national exhibition network consisting of movie theaters, workers' clubs and mobile film projections to bring film to the people. One figure that soon caught the attention of national media was the film projectionist, who traditionally occupied a marginal position in the film industry. Meanwhile, Mao Zedong's 'Talks at the Yan'an Forum of Literature and Arts' was held as a guiding document for all cultural workers, who were expected to 'serve the people' by both making culture accessible to the masses and teaching them to be socialist subjects. This paper proposes to see the film projectionist as an embodiment of Chinese socialist cultural ideals that had roots in Mao's 'Talks'. Previous scholarship has paid little attention to film exhibition during the 17 years period (1949–1966). Using newspapers, magazines and government documents, I detail exhibition practices and screening procedures that Maoist film projectionists were instructed to follow. I argue that as an ideal figure, the projectionist integrated mass entertainment and education by simultaneously playing the roles of the people's servant, the party propagandist and the film lecturer.